The development of risk management elements (APR) for Forest-Friendly Pedagogy (PERIMBA) as a guide for indigenous school teacher. Issue 1 (April 2021) - Haron, M N; Wahab, N B A; Kasim, R; Abdullah, N; Bohari, N M
Abstract: The Forest-friendly pedagogy (PERIMBA) refers to the implementation of outdoor learning session by using forest elements as the learning aid and site. In promoting meaningful learning especially to the indigenous school, PERIMBA's introduces a risk-taking approach that will offer the opportunities for teachers and pupils to engage in risky activities during learning session. The input on risk and risk perception will be an added value to teachers to implement PERIMBA in their teaching and learning sessions. However, PERIMBA's needs further research and study especially in the field of risk. These concepts then lead to risk perception that, in turn, influenced risk management. The purpose of this study is to identify risk management element for forest-friendly pedagogy (PERIMBA) at Indigenous School. To achieve this goal, this study is conducted qualitative in the form of analysis document. A few of previous document, survey report, conference proceeding, and journal had been referred as literature study, and analysed with data gathered use schedule matric. The finding shows that there are three elements which are risk identification, risk assessment and risk control.